Alterations in cerebral and cardiac mitochondrial function in a porcine model of acute carbon monoxide poisoning. (2nd September 2021) - Jang, David H.; Piel, Sarah; Greenwood, John C.; Kelly, Matthew; Mazandi, Vanessa M.; Ranganathan, Abhay; Lin, Yuxi; Starr, Jonathan; Hallowell, Thomas; Shofer, Frances S.; Baker, Wesley B.; Lafontant, Alec; et al.
Abstract: Objectives: The purpose of this study is the development of a porcine model of carbon monoxide (CO) poisoning to investigate alterations in brain and heart mitochondrial function. Design: Two group large animal model of CO poisoning. Setting: Laboratory. Subjects: Ten swine were divided into two groups: Control ( n = 4) and CO ( n = 6). Interventions: Administration of a low dose of CO at 200 ppm to the CO group over 90 min followed by 30 min of re-oxygenation at room air. The Control group received room air for 120 min. Measurements: Non-invasive optical monitoring was used to measure cerebral blood flow and oxygenation. Cerebral microdialysis was performed to obtain semi real time measurements of cerebral metabolic status. At the end of the exposure, both fresh brain (cortical and hippocampal tissue) and heart (apical tissue) were immediately harvested to measure mitochondrial respiration and reactive oxygen species (ROS) generation and blood was collected to assess plasma cytokine concentrations. Main results: Animals in the CO group showed significantly decreased Complex IV-linked mitochondrial respiration in hippocampal and apical heart tissue but not cortical tissue. There also was a significant increase in mitochondrial ROS generation across all measured tissue types. The CO group showed a significantly higher cerebral lactate-to-pyruvate ratio. Both IL-8 and TNFα were significantly increased in the CO group compared with the Control group obtained from plasma. While not significant there was a trend to an increase in optically measured cerebral blood flow and hemoglobin concentration in the CO group. Conclusions: Low-dose CO poisoning is associated with early mitochondrial disruption prior to an observable phenotype highlighting the important role of mitochondrial function in the pathology of CO poisoning. This may represent an important intervenable pathway for therapy and intervention.